Comparison of hydroxyethyl starch regulatory summaries from the Food and Drug Administration and the European Medicines Agency - Christian J. Wiedermann; Klaus Eisendle (Journal of Pharmaceutical Policy and Practice, 2017)
This article aims to highlight the positions of the Food and Drug Administration and the European Medicines Agency regarding use and marketing of hydroxyethyl starch (HES) products, and how these have changed over recent years. In 2013, warnings from both agencies advised against use of HES in critically ill patients, including patients with sepsis, when several large randomized controlled trials on volume resuscitation in critical illness failed to observe clinically beneficial effects of HES. In areas such as patient monitoring and requirements for further clinical trials, the FDA and EMA are very much in agreement in their recommendations. However, EMA guidance is generally more restrictive on HES usage compared to that from the FDA. Differences in data presented to regulatory authorities, bias in study results and inherent weakness of meta-analyses used for drug surveillance purposes, plus different risk-management approaches used by the two regulatory authorities, likely contribute to different outcomes in their regulations concerning use of HES.